SEJARAH KESUKSESAN NABI MUHAMMAD SAW DALAM MEMIMPIN DAKWAH - Safrudin, Irfan; Shiddiq, Asep Ahmad; Muttaqin, Ahmad (HIKMAH : Jurnal Dakwah Dan Sosial, 2025)
The Da'wah of the Prophet Muhammad was not only limited to spiritual and social aspects, but also included the fields of politics and government. This research aims to examine how the history of the Prophet Muhammad's success in leading da'wah, especially in the state. By using a descriptive qualitative method based on literature study, this research reveals that the Prophet Muhammad SAW successfully led da'wah in the state applying the principles of equality and togetherness, rejecting tyranny, maintaining law, providing religious freedom, and upholding the rule of law that had been established and agreed upon. Dakwah Nabi Muhammad SAW tidak hanya terbatas pada aspek spiritual dan sosial, tetapi juga mencakup bidang politik dan pemerintahan. Penelitian ini bertujuan untuk mengkaji bagaimana sejarah kesuksesan Nabi Muhammad dalam memimpin dakwah khususnya dalam bernegara. Dengan menggunakan metode deskriptif kualitatif berbasis studi pustaka, penelitian ini mengungkap bahwa Nabi Muhammad SAW berhasil memimpin dakwah dalam bernegara menerapkan prinsip-prinsip kesamaan dan kebersamaan, menolak tirani, memelihara hukum, memberikan kebebasan keagamaan, dan menjunjung tinggi supremasi hukum yang telah ditetapkan serta disepakati.